The impact of 'high-failure rate' mathematics courses on UiTM sarawak full-time diploma students' academic performance / Tang Howe Eng ... [et al.] - Tang, Howe Eng; Voon, Li Li; Julaihi, Nor Hazizah (2008)
This research seeks to analyze the impact of UiTM Sarawak full-time diploma students' academic performance on the 'high-failure rate' Mathematics courses. The respondents consisted of the full-time diploma students in UiTM Sarawak who had taken the 'high-failure rate' Mathematics courses, lecturers who had taught the 'highfailure rate' Mathematics courses and students who had taken those courses. The instruments comprised the report of final examination analysis, students' particulars in the registration database, the database of total credit hours for courses offered in each programme and questionnaires